1998
DOI: 10.1111/j.1600-051x.1998.tb02362.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased bFGF level in the serum of patients with phenytoin‐induced gingival overgrowth

Abstract: To elucidate the involvement of bFGF (basic fibroblast growth factor) in the pathogenesis of phenytoin-induced gingival overgrowth, we measured the concentration of bFGF in the serum of 36 epileptic patients taking phenytoin and in 94 normal volunteers by enzyme-linked immunosorbent assay technique. The concentration of phenytoin in serum was determined by high-performance liquid chromatography. In 34 of 36 patients taking phenytoin in this investigation, apparent gingival overgrowth was noticed. The mean conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 45 publications
0
16
1
Order By: Relevance
“…These findings are of great interest, and suggest that substances that cause gingival overgrowth may do so by altering the normal balance of cytokines in gingival tissues. Cytokines and growth factors found at elevated levels in human drug-induced gingival overgrowth include interleukin-6 (IL-6), IL-1␤, platelet-derived growth factor-B (PDGF-B), fibroblast growth factor-2 (FGF-2), transforming growth factor-␤ (TGF-␤), and connective tissue growth factor (CTGF) (Williamson et al, 1994;Nares et al, 1996;Plemons et al, 1996;Saito et al, 1996;Dill and Iacopino, 1997;Iacopino et al, 1997;Atilla and Kutukculer, 1998;Sasaki and Maita, 1998;Hong et al, 1999;Myrillas et al, 1999;Buduneli et al, 2001;Uzel et al, 2001).…”
Section: Cytokines and Drug-induced Gingival Overgrowthmentioning
confidence: 99%
“…These findings are of great interest, and suggest that substances that cause gingival overgrowth may do so by altering the normal balance of cytokines in gingival tissues. Cytokines and growth factors found at elevated levels in human drug-induced gingival overgrowth include interleukin-6 (IL-6), IL-1␤, platelet-derived growth factor-B (PDGF-B), fibroblast growth factor-2 (FGF-2), transforming growth factor-␤ (TGF-␤), and connective tissue growth factor (CTGF) (Williamson et al, 1994;Nares et al, 1996;Plemons et al, 1996;Saito et al, 1996;Dill and Iacopino, 1997;Iacopino et al, 1997;Atilla and Kutukculer, 1998;Sasaki and Maita, 1998;Hong et al, 1999;Myrillas et al, 1999;Buduneli et al, 2001;Uzel et al, 2001).…”
Section: Cytokines and Drug-induced Gingival Overgrowthmentioning
confidence: 99%
“…This might, in some degree, explain why not all phenytoin-treated individuals develop gingival enlargement. Recently, several reports revealed that the pathogenesis of phenytoin-induced gingival enlargement might be related to certain cytokines, including interleukin-1, -6, and -8; platelet-derived growth factor BB; and basic fibroblast growth factor (Hong & Trackman, 2002;Modeer et al, 2000;Sasaki & Maita, 1998). Whether similar mechanisms play a role in valproate-induced gingival enlargement is unclear.…”
Section: Periodontal Problemsmentioning
confidence: 99%
“…As increased levels of FGF-2 may be found in the blood of patients with liver cirrhosis, 7 in phenytoin-treated patients suffering from epilepsy, 8 and in patients with systemic sclerosis and dermatomyositis, 9 we therefore checked for these diseases in the clinical history of CML and B-CLL patients. None of the individuals involved in this study suffered from any of those diseases and/or from tumor duplicity at the time of collection of peripheral blood.…”
Section: Levels Of Fgf-2 Are Elevated In Plasma Of CML and B-cll Patimentioning
confidence: 99%